Exercise, circadian rhythms, and muscle regeneration: a path to healthy aging - Su, Zhanguo; Xiang, Lijuan (Frontiers in Neuroscience, 2025)
The circadian system regulates core physiological processes, including muscle regeneration, protein synthesis, and cellular homeostasis. Disruptions in circadian rhythms contribute to impaired muscle function in older adults, with age-related declines in muscle mass and regenerative capacity serving as major contributors to sarcopenia. Emerging evidence indicates that exercise—a powerful modulator of muscle adaptation—can also influence circadian regulation, offering a potential avenue to enhance muscle repair in aging populations. This review examines how physical activity interacts with circadian mechanisms in aged skeletal muscle, emphasizing key molecular and cellular pathways involved in muscle regeneration. Central circadian regulators such as Clock, BMAL1, and PER1 are discussed in the context of muscle protein turnover, satellite cell activity, and mitochondrial function. Aligning exercise timing with circadian rhythms is proposed as a promising strategy to enhance muscle recovery and functional capacity in older individuals. Furthermore, the review highlights the therapeutic potential of chrono-exercise to delay the onset of sarcopenia and promote healthy aging. By integrating insights from chronobiology, geroscience, and exercise physiology, this analysis underscores the importance of chrono-exercise in supporting muscle health during aging.